Pemberdayaan Masyarakat dalam Peningkatan Kualitas Pemukiman melalui Pengelolaan Infrastruktur Sanitasi Desa Tunggulo - Rawiyah Husnan; Frice L. Desei; Marike Mahmud (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2026)
Tunggulo Village is one of the villages in the West Limboto District of Gorontalo Regency. Tunggulo village is facing several fundamental problems that affect the quality of life of its people. Tunggulo village is facing serious obstacles in waste management and wastewater disposal system (SPAL). The implementation of the Infrastructure Thematic Real Work Lecture has been held through a participatory approach that provides direct education to the community. The result of the community's active involvement in the Infrastructure Thematic Real Work Lecture is the creation of an IMAP Map (Problem Identification and Potential Analysis) in the form of mapping the conditions related to sanitation infrastructure (Unfit Houses (RTLH), garbage and Wastewater Treatment System SPAL)). Regarding waste, the calculation of household waste generation in Tunggulo Village has also been carried out with the weight of waste generation amounting to 1137.15 kg per day or with a volume of 6.06 m3 per day. As a follow-up, the solutions to the next problems are compiled into a medium and long-term development plan for the procurement program of quality housing for healthy homes, waste bins, TPS, TPS3R, waste banks compost, which can provide good impact solutions to village problems in terms of RTLH, stunting and sanitation. The formation of the Waste Management Task Force is expected to help coordinate with related parties and partners and sustainable waste management.